PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 85 PEKANBARU - Teguh Arif Satrianto; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is students lower score in learning social of class IIIC SDN 85 Pekanbaru, it can be seen from 23 students of class III C, 17 students (73,91%) got lower score and 6 students (26,08%) got higher score with the mean score is 61,30. The KKM of this school is 75. According to the problem, the researcher has conducted a classroom action research by implementing Inquiry Guide model. In cycle I, the percentage of teacher’s activity in first meeting is adequate 61%. In the second meeting, it increased to 73% with good category. In cycle II, first meeting it increased to 91% with good category in first meeting and second meeting indicated in very good category 99%. In cycle I, the percentage of student’s activity in first meeting is adequate 56%. In the second meeting, it increased to 70% with good category. In cycle II, first meeting it increased to 87% with good category in first meeting and second meeting indicated in very good category 99%. An average score of student’s learning result before implementation Inquiry Guide model was 61,30% it increase to 62,00% in cycle I, and 88,48% in cycle II. The classical completeness was achieved in both cycle. In conclusion, the implementation Inquiry Guide model can improve student’s learning result in social subject of class III C of SDN 85 Pekanbaru. Key Words: Inquiry Guide model, learning outcames IPA